Metacognitive Strategies for Reading Comprehension and Oral Expression Skills of Second English Students, URACCAN, first semester, 2023 - Mejía Meza, Zaharen Gabrie; González García, Xochil Johelsi; Freddy Javier Chamorro Sady (tutor) (Nicaragua: URACCAN, 2023)
Monografía de ingles, Estrategias de Educación
Incluye Bibliografía, Imágenes, Gráficos
Col. Mon.
Keywords: 1.MONOGRAFIA DE INGLES 2.ESTRATEGIAS COGNITIVAS 3. COMPRENSION LECTORA